Succession characteristics of phytoplankton functional groups and water quality responsiveness evaluation in an artificial constructed wetland-reservoir ecosystem. Issue 1 (31st December 2022) - Ma, Zhiqiang; Ma, Weixing; Li, Xuan; Li, Zhaoxia; Pan, Mei; Ding, Cheng
ABSTRACT: The artificial constructed wetland-reservoir ecosystem has become a research hotspot in the field of the pretreatment of micro-polluted water. In this study, the water purification efficiency and phytoplankton dynamics, the succession characteristics of phytoplankton functional groups and water quality responsiveness evaluation were investigated. The results showed that the Yanlong project can effectively purify water, and there were significant spatial differences in DO, pH, turbidity and transparency ( P <0.001), while the temporal differences in water temperature, DO, electrical conductivity, TP and NH4 + -N were the most significant ( P< 0.001). B, D, P, MP, X1, J and Lo were consistently dominant FGs, Group I, Group IV, Group V and Group VI were dominant MBFGs throughout the year. The results indicated that MBFG was better than that of the FG while water temperature, pH and BOD5 were the key environmental factors. Overall, our findings could provide important implications to improve sustainable safety of drinking water sources.